Five-Year Follow-Up of Distal Tibia Bone and Foot and Ankle Trauma Treated with a 3D-Printed Titanium Cage - Eugene C. Nwankwo; Fangyu Chen; Dana L. Nettles; Samuel B. Adams (Case Reports in Orthopedics)
Large bone defects from trauma or cancer are difficult to treat. Current treatment options include the use of external fixation with bone transport, bone grafting, or amputation. These modes of therapy continue to pose challenges as they are associated with high cost, failure, and complication rates. In this study, we report a successful case of bone defect treatment using personalized 3D-printed implant. This is the longest known follow-up using a 3D-printed custom implant for this specific application. Ultimately, this report adds to existing literature as it demonstrates successful and maintained incorporation of bone into the titanium implant. The use of patient-specific 3D-printed implants adds to the available arsenal to treat complex pathologies of the foot and ankle. Moreover, the technology’s flexibility and ease of customization makes it conducive to tailor to specific patient needs.